Nomograms Predicting Survival of Cervical Cancer Patients Treated With Concurrent Chemoradiotherapy Based on the 2018 FIGO Staging System - Meng, Qingyu; Wang, Weiping; Liu, Xiaoliang; Wang, Dunhuang; Zhang, Fuquan (Frontiers in Oncology, 2022)
Background: In 2018, a revised staging system was released for cervical cancer, which defined pelvic and para-aortic lymph node metastasis as stage IIIC1 and IIIC2, respectively. In this study, we constructed and validated nomograms to predict the 3-year and 5-year survival of patients with cervical cancer based on this revised the International Federation of Gynecology and Obstetrics (FIGO) staging system. Methods: We retrospectively analyzed patients with 2009 FIGO stage IB-IVA cervical cancer who were treated at our institute between 2011 and 2015. Patients were randomized into the model development and validation cohorts (2:1). Univariate and multivariate analyses were conducted in the model development cohort to identify prognostic factors. In multivariate analysis, nomograms were built to predict overall survival (OS) and disease-free survival (DFS) using significant variables. The nomograms were assessed based on the discrimination and calibration in both cohorts. Discrimination was assessed using the concordance index. Calibration was performed by comparing the mean nomogram estimated survival and the mean observed survival. Results: We included 1192 patients, with 795 and 397 patients in the model development and validation cohorts, respectively. In the model development cohort, the median follow-up period was 49.2 months. After multivariate analysis, age, histology, 2018 FIGO stage, and pelvic lymph node number were independent factors for OS. Histology, 2018 FIGO stage, SCC antigen, and pelvic lymph node number were significant predictors of DFS. The nomograms constructed to predict OS and DFS were based on these factors. In model both cohorts, the concordance index for the nomograms predicted OS and DFS were 0.78 and 0.75, and 0.74 and 0.67, respectively. The calibration curve revealed good agreement between the nomogram predictions and actual values. Conclusion: We constructed robust nomograms to predict the OS and DFS of patients with cervical cancer undergoing treatment with concurrent chemoradiotherapy based on the 2018 FIGO staging system.